ERROR ANALYSIS ON ENGLISH DEPARTMENT STUDENTS’ THESIS BACKGROUNDS - Dita Yohana Sara Simanjuntak; Sri Minda Murni; Yeni Erlita (Universitas Negeri Medan, 2019)
This study deals with the Error Analysis on English Department Students’ Thesis Backgrounds in State University of Medan. The objective of this research are: 1. To find the types of errors are frequently found in thesis background written by graduated students of English department at State University of Medan. 2. To find the source of the errors that found in the thesis background of graduated students of English Department. Related to the object of the research, the researcher used the descriptive qualitative method. The research was conducted at Reading Room Faculty of Lamguages and Arts. The object of this research is 30 theses. The result of this research showed that there are 103 errors of Misformation that happened because the students write the sentences in present tense, while the thesis background study has to be written in past tense. The highest recapitulation showed that the most source of error is “intralingual transfer”. Keywords: error analysis, thesis backgrounds